Clinical Phenotypes of Hypoxia in Patients with COVID-19 - O. V. Voennov; A. V. Turentinov; K. V. Mokrov; P S. Zubееv; S. A. Abramov (Общая реаниматология, 2021)
The aim of the study was to examine the clinical phenotypes of hypoxia in patients with COVID-19 in relation to the severity of acute respiratory failure (ARF).Material and methods. Sixty patients with severe COVID-19 and manifestations of acute respiratory failure admitted to the infectious disease hospitals of Nizhny Novgorod were enrolled in the study.The study included patients with transcutaneous saturation (SpO2) below 93% on spontaneous breathing, who required correction of respiratory alterations according to the Interim Clinical Guidelines for the Treatment of Patients with COVID-19. All patients were divided into 2 groups of 30 patients each according to the nature of respiratory impairment. Group 1 included patients without breathing difficulties who had respiratory rate up to 25 per minute. Group 2 patients had breathing difficulties and respiratory rate over 25 per minute.In addition to SpO2, severity of respiratory difficulties, respiratory rate (RR), forced breathing (FB), heart rate (HR), acid-base balance (ABB) and arterial and venous blood gases, capillary refill time, blood lactate level were assessed. The severity of lung involvement was determined using chest computed tomography, and severity of disease was assessed using the NEWS score. Respiratory treatment required for ARF correction and the outcome of hospitalization were also considered.Results. In group 1, the mean age was 66 (56; 67) years and the disease severity was 8 (7; 10) points. Group 1 patients had minor tachycardia and tachypnoea, there were no lactate elevation or prolonged capillary refill time. Mean SpO2 was as low as 86 (83; 89)%. Venous blood pH and pCO2 values were within normal reference intervals, mean BE was 6 (4; 9) mmol/l, pO2 was 42 (41; 44) mm Hg, and SO2 was 67 (65; 70)%. Mean arterial blood pO2 was 73 (69; 75) mm Hg, SO2 was 86 (83; 90)%, and O2 was 37 (35; 39) mm Hg. Oxygen therapy with the flow rate of 5-15 l/min in prone position helped correct ARF. All patients of this group were discharged from hospital.In group 2, the mean age was 76 (70;79) years and the disease severity was 14 (12; 18) points. Anxiety was observed in 15 patients, prolonged capillary refill time was seen in 13 patients, and increased lactate level in 18 patients. Mean RR was 34 (30; 37) per minute, HR was 110 (103; 121) per minute, and SpO2 was 76 (69; 83)%. Mean venous blood pH was 7.21 (7.18; 7.27), pCO2 was 69 (61; 77) mm Hg, BE was -5 (-7; 2) mmol/l, pO2 was 25 (22; 28) mm Hg, SO2 was 47 (43; 55)%. Mean arterial blood pO2 was 57 (50; 65) mm Hg, SO2 was 74 (69; 80)%, and pCO2 was 67 (58; 74) mm Hg. In the group 2 patients, the standard oxygen therapy in prone position failed to correct ARF, and high flow oxygen therapy, noninvasive CPAP with FiO2 of 50-90% or noninvasive CPAP+PS were administered. Fourteen patients were started on invasive lung ventilation. There were 10 fatal outcomes (33%) in this group.Conclusion. Two clinical phenotypes of hypoxia in patients with COVID-19 can be distinguished. The first pattern is characterized by reduced SpO2 (80-93%), no tachypnoea (RR >25 per minute) and moderate arterial hypoxemia without tissue hypoxia and acidosis («silent hypoxia»). It is typical for younger patients and associates with less lung damage and disease severity than in patients with severe ARF. Hypoxemia can be corrected by prone position and oxygen therapy and does not require switching to mechanical ventilation. The second pattern of hypoxia is characterized by significant arterial hypoxemia and hypercapnia with tissue hypoxia and acidosis. Its correction requires the use of noninvasive or invasive mechanical ventilation.